(3EOGQI GdJaGhVs - (3SGeM YHO GdeWdH(B, (3YGeQs; (3YdGA eMeO SjO bfOjd(B, s ((3YeGf(B:s (3OGQ GdacQ ddfTQ hGdJhRjY(B,s, 2011)
(3eONd Edi GdJaGhV, GdJaGhV GdLeGYj h GdGLJeGYj aj VhA GdYdGbI Hjf GdefXeI h GdeLJeY, GdJaGhV h Md GdUQGYGJ OGNd GdefXeI, GdJaGhV aj GJNGP GdbQGQGJ h Md GdeTcdGJ, GdJaGhV h Md GdeTcdGJ GdGOGQjI OGNd GdefXeI, fXe GdeYdheGJ GdJaGhVjI, GdGOGQI GdeYdheGJjI aj YedjI GdJaGhV, GdJYGbOGJ h GdGOGQI GdJaGhVjI, GdJaGhV eY GdLgGJ GdNGQLjI, GdJaGhV aj YedjGJ GdTQGA, GdJaGhV h YedjGJ GdHjY h cSH h GSJKeGQ GdYedGA, GSJQGJjLjI GdMUhd Ydi GdehGabI QZe JVGQH GdeUGdM , GdbjGOI GdJaGhVjI bjGOI aQjb GdYed (B( (3GdJaGhV GdebGO(B) (3, eJWdHGJ GdJaGhV aj VhA GdYhdeI, GdJaGhV Ydi GdeSJhi GdOhdj h GdeYGedGJ GdOhdjI, GOGQI GdJaGhV aj GdYdGbGJ GdOhdjI (B((3QDjI bGfhfjI (B)s
(3cTGa eUWdMGJ HGddZI GdGfLdjRjI U(B.459 (3HHdjhZQGajG(B: (3U(B.437s
Keywords: (3EOGQI GdCaQGOs; (3GdeaGhVGJs